Lysosome Sensing Is a Key Mechanism in Leishmania Intracellular Development - Zilberstein, Dan (Frontiers in Microbiology, 2021)
Phagolysosomes of macrophages are the niche where the parasitic protozoan Leishmania resides and causes human leishmaniasis. During infection, this organism encounters dramatic environmental changes. These include heat shock (from 26°C in the vector to 33°C or 37°C in the host, for cutaneous and visceral species, respectively) and acidic pH typical to the lysosome and nutrient availability. Leishmania cells developed ways to sense the lysosome-specific environment (acidic pH and body temperature) as means of recognition and, subsequently, initiation of differentiation into the intracellular form. Recent studies have indicated that protein kinase A plays a role as the gatekeeper that enables differentiation initiation. This review provides an update on the lysosome signaling pathway-mediated Leishmania intracellular development.